2015
DOI: 10.1186/s12970-014-0064-5
|View full text |Cite
|
Sign up to set email alerts
|

Pea proteins oral supplementation promotes muscle thickness gains during resistance training: a double-blind, randomized, Placebo-controlled clinical trial vs. Whey protein

Abstract: BackgroundThe effects of protein supplementation on muscle thickness and strength seem largely dependent on its composition. The current study aimed at comparing the impact of an oral supplementation with vegetable Pea protein (NUTRALYS®) vs. Whey protein and Placebo on biceps brachii muscle thickness and strength after a 12-week resistance training program.MethodsOne hundred and sixty one males, aged 18 to 35 years were enrolled in the study and underwent 12 weeks of resistance training on upper limb muscles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
108
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 42 publications
9
108
1
3
Order By: Relevance
“…In comparison, 5 other studies demonstrated equivalent increases in vastus lateralis myofiber CSA in protein supplemented treatments [whey protein (n=3), milk (n=1) or EAA (n=1)] and carbohydrate placebo treatments (6, 9, 23, 31, 32). In addition, studies utilizing MRI of the biceps (10) or latissimus dorsi (33) and ultrasound (3, 4, 22, 23, 48) of the thigh muscles have clearly shown the same pattern; no effect of protein supplementation (whey) to enhance vastus lateralis muscle hypertrophy. Given these findings, it is no surprise that only one study on protein supplementation showed an enhancement of strength, even though myofiber CSA was not different with protein supplementation (9).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, 5 other studies demonstrated equivalent increases in vastus lateralis myofiber CSA in protein supplemented treatments [whey protein (n=3), milk (n=1) or EAA (n=1)] and carbohydrate placebo treatments (6, 9, 23, 31, 32). In addition, studies utilizing MRI of the biceps (10) or latissimus dorsi (33) and ultrasound (3, 4, 22, 23, 48) of the thigh muscles have clearly shown the same pattern; no effect of protein supplementation (whey) to enhance vastus lateralis muscle hypertrophy. Given these findings, it is no surprise that only one study on protein supplementation showed an enhancement of strength, even though myofiber CSA was not different with protein supplementation (9).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the data are limited and a firm conclusion is hard to form regarding an advantage to supplementation with whey protein over other protein sources. Since the publication of this meta-analysis [ 16 ] there have been studies published in which whey protein has been compared to soy protein [ 15 ], pea protein [ 63 ], and rice protein [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…Babault and colleagues [ 63 ] conducted a study in young men consuming either a placebo, pea protein, or whey protein. This study was a large-scale trial in which 137 subjects were included for analysis ( n = 47, 46, and 44, respectively for the placebo, pea protein, and whey protein concentrate supplemented group).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, whereas the DIAAS for milk, eggs and beef are well above 100%, plant-derived proteins generally score well below 80%. Nonetheless, some protein extracts obtained from soy, 27 rice 28 or pea 29 have demonstrated scores closer or above 100%. Figure 1 indicates that when the same amount of protein is consumed, whey isolate extracts provide more IAA, including leucine, compared with other animal (casein, egg, beef, insect or bovine colostrum) and plant (hemp, pea, brown rice) protein products.…”
Section: Whey Protein Quality: Bioavailability and Aa Profilementioning
confidence: 99%